2019
DOI: 10.1016/j.neuropharm.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Orexin/hypocretin receptor gene (HCRTR1) variation is associated with aggressive behaviour

Abstract: Highlights• Orexins are involved in the regulation of stress response • The HCRTR1 rs2271933 G>A genotype was associated with aggressiveness • A/A homozygotes were more aggressive and relapsed to drunk driving • A-allele carriers were more frequently involved in traffic accidents• The genotype effect is sensitive to stressful life events AbstractOrexins, alternatively called hypocretins, are neuropeptides with crucial role in maintaining wakefulness. The orexin system is thought to mediate a coordinated defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The Reward Openness and Insatiability Scale (ROIS) that is used in this manuscript to measure reward sensitivity was constructed post hoc making use of previously collected information on personality. Three experienced behavioural scientists independently extracted items thought to reflect reward sensitivity from the Estonian versions of International Personality Item Pool NEO (IPIP) (Goldberg, 1999;Mõttus et al, 2006), Barratt Impulsiveness Scale (BIS-11;Patton et al, 1995;Akkermann et al, 2010), the brief version of the ANPS (Davis et al, 2003;Harro et al, 2019), Spielberger State-Trait Anxiety Inventory (STAI; Spielberger et al, 1983;Akkermann et al, 2010), and Adaptive and Maladaptive Impulsivity Scale (AMIS) (Paaver et al, 2006;Tomson-Johanson et al, 2020). The extracted items were discussed, and an initial pool of items was formed with consensus.…”
Section: Reward Openness and Insatiability Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The Reward Openness and Insatiability Scale (ROIS) that is used in this manuscript to measure reward sensitivity was constructed post hoc making use of previously collected information on personality. Three experienced behavioural scientists independently extracted items thought to reflect reward sensitivity from the Estonian versions of International Personality Item Pool NEO (IPIP) (Goldberg, 1999;Mõttus et al, 2006), Barratt Impulsiveness Scale (BIS-11;Patton et al, 1995;Akkermann et al, 2010), the brief version of the ANPS (Davis et al, 2003;Harro et al, 2019), Spielberger State-Trait Anxiety Inventory (STAI; Spielberger et al, 1983;Akkermann et al, 2010), and Adaptive and Maladaptive Impulsivity Scale (AMIS) (Paaver et al, 2006;Tomson-Johanson et al, 2020). The extracted items were discussed, and an initial pool of items was formed with consensus.…”
Section: Reward Openness and Insatiability Scalementioning
confidence: 99%
“…We used the adaptation (Harro et al, 2019) of the short version of the ANPS (Davis et al, 2003) that is a self-report instrument constructed bottom up to correspond to the activity in neural circuits underlying basic emotive systems as defined in animal research (Panksepp, 1998;Davis and Panksepp, 2011). It comprises scales termed ANGER, FEAR, SADNESS, SEEKING, CARE, and PLAY, each measured with six items, each on a 5-point scale.…”
Section: Affective Neuroscience Personality Scalementioning
confidence: 99%
“…Nevertheless, when performing subgroup analyses by ethnicity, age of participants, sample characteristics, and outcome measures, significant associations emerge (6). Several variants in a number of candidate genes have been found strongly associated with aggression measures in the ECPBHS sample [see (29,33) and references therein]. It should hence be concluded that in this specific population of which the ECPBHS sample is highly representative, other genes than RBFOX1 play a role in aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…ECPBHS is population representative, while 79.1% of subjects of the randomized regional sample participated in the original sampling. Details on follow-ups have been described elsewhere [e.g., (29)], and the number of participants in the presented analyses is given below. The study was approved by the Ethics Review Committee on Human Research of the University of Tartu.…”
Section: Study Populationmentioning
confidence: 99%
“…Orexin release modulates the expression and extinction of fear memories (Flores et al, 2015) and the orexin neurons are activated in acute response to a variety of stressors; however, their role in chronic stress appears complex (Sargin, 2019), leading to the hypothesis that the role for orexins in neurotransmission is promoted during aversive conditions that elicit high arousal (Berridge et al, 2010). We have recently found evidence for a role of orexins in the other side of the flight/fight response, aggressiveness, by association of the HCRTR1 gene encoding the orexin OX1 receptor (Harro et al, 2019). The HCRTR1 gene variant (rs2271933, G1222A) in exon 7 that leads to amino acid substitution (Ile408Val) (Meerabux et al, 2005) was linked to aggressive behaviour or breach of law in four independent population samples by use of self-reports, interviews, and databases.…”
Section: Introductionmentioning
confidence: 99%